(untitled) (Scientific journal of the Fergana State University, 2023)
In this article author revealed the hart pace of our economy in the previous years of our independence. At that intense time, the exigency of energy in was republic increased. Also indicated the interesting of foreigner investors towards current plant promotes the oil independence of Uzbekistan. Besides that shown the decisions of The Supreme Court on working with totally quality and power.